If not quality, then what? The discursive risks in early childhood quality reform. Issue 6 (2nd November 2019) - Hunkin, Elise
ABSTRACT: This paper reports on the findings of a genealogical study and argues that the global discourse of quality in early childhood education and care (ECEC) is based on a number of problematic assumptions that converge to identify 'quality' as the site of government investment. Using the Australian policy context as an example, the assumption that only quality ECEC is beneficial for children is linked to the historical privileging of mother-care and the male breadwinner through family policy. Using Foucault's notion of the 'art of government', the implications of the discursive logics of quality are outlined, including how 'not quality' childcare is positioned as potentially harmful, yet, the workforce can never be 'quality enough'. It is recommended that early childhood sector academics, advocates and professionals work to introduce new discursive statements to the global policyscape, in order to create and foster diverse representations and understandings of the benefits and value of ECEC.